Pengaruh Pendidikan Kesehatan Senam Nifas Terhadap Pengetahuan Primipara Tentang Senam Nifas di Wilayah Kerja Puskesmas Lubuk Buaya Padang: The Effect of Postpartum Gymnastics Health Education on Primiparous Knowledge about Postpartum Gymnastics in Lubuk Buaya Health Center Working Area Padang - Febri Wendari; Vetty Priscilla; Wedya Wahyu (Fakultas Keperawatan Universitas Andalas, 2013)
Puerperal is an important activity done after childbirth, one of the goals to prevent complications at a time puerperal. To increase the knowledge of mothers after childbirth mainly primipara about puerperal exercise is through health education. The aim of the research is to know the effect of puerperal exercise health education on primipara knowledge about puerperal exercise in lubuk buaya health center padang 2013. This research uses a quasi-experimental approach to pre-posttest design, with a sample of 19 primipara. Retrieval of data started from February 23 to March 22, with sampling purposive sampling using questionnaire. Analizyng the data is using Wilcoxon. The result showed that the primipara that have a good knowledge of as much(10,5%)before being given the health education, after given a puerperal exercise healt education, primipara that have a knowledge of good as much (84,2%). The result of statistical test showed the influence of puerperal execercise health education of knowledge (p=0,000). Advice to the clinic to be able to make a puerperal exercise routine program of restoring the health of mothers after childbirth.